An assessment of techniques for the characterisation of cynodon turfgrasses - Laminski, Sandra. (My University, 1990)
The genus Cynodon within the Chloridoideae of the Poaceae is a small genus. cynadon are among the most highly valued warm season turfgrasses in the world, because of their good drought resistance and recuperative potential, their high density and good colour (Beard 1973). Due to modern plant breeding efforts, cultivated plants develop towards uniform entities which are difficult to distinguish at the cultivar level. Methods that are traditionally used in cultivar identification vary depending on plant type. Currently identification of turf Cynodon cultivars is based on morphological, physiological and cytological charaters. Although these methods of cultivar identification are satisfactory, they are not ideal, as the tests are fairly time consuming and some of the phenotypic differences are difficult to measure. (Abbreviation abstract)
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of MSc
Keywords: Cynodon.; Grasses -- South Africa.; Plant genetics.; Plant cytogenetics.